Icosahedral metallacarborane/carborane species derived from 1, 1′-bis(o-carborane)12. Issue 12 (23rd February 2015) - Thiripuranathar, Gobika; Man, Wing Y.; Palmero, Cesar; Chan, Antony P. Y.; Leube, Bernhard T.; Ellis, David; McKay, David; Macgregor, Stuart A.; Jourdan, Laure; Rosair, Georgina M.; Welch, Alan J.
Abstract : Both unisomerised and isomerised singly-metallated derivatives of 1, 1′-bis( o -carborane) with both Ru(arene) and (CoCp